A nomogram of clinical and biologic factors to predict survival in children newly diagnosed with high‐risk neuroblastoma: An International Neuroblastoma Risk Group project. Issue 3 (18th November 2020) - Moreno, Lucas; Guo, Dongjing; Irwin, Meredith S.; Berthold, Frank; Hogarty, Michael; Kamijo, Takehiko; Morgenstern, Daniel; Pasqualini, Claudia; Ash, Shifra; Potschger, Ulrike; Ladenstein, Ruth; Valteau‐Couanet, Dominique; et al.
Abstract: Background: Long‐term outcome remains poor for children with high‐risk neuroblastoma (five‐year overall survival [OS] ∼50%). Our objectives were to (a) identify prognostic biomarkers and apply them in a nomogram to identify the subgroup of ultra‐high‐risk patients at highest risk of disease progression/death, for whom novel frontline therapy is urgently needed; and (b) validate the nomogram in an independent cohort. Methods: A total of 1820 high‐risk patients (≥18 months old with metastatic neuroblastoma), diagnosed 1998‐2015, from the International Neuroblastoma Risk Groups (INRG) Data Commons were analyzed in a retrospective cohort study. Using multivariable Cox regression of OS from diagnosis, a nomogram was created from prognostic biomarkers to predict three‐year OS. External validation was performed using the SIOPEN HR‐NBL1 trial cohort ( n  = 521), evidenced by receiver operating characteristic curves. Results: The nomogram, including MYCN status ( P  < 0.0001), lactate dehydrogenase (LDH) ( P  = 0.0007), and presence of bone marrow metastases ( P  = 0.004), had robust performance and was validated. Applying the nomogram at diagnosis (a) gives prognosis of an individual patient and (b) identifies patients predicted to have poor outcome (three‐year OS was 30% ± 5% for patients with a nomogram score of > 82 points; 58% ± 1% for those ≤82 points). Median follow‐up time was 5.5 years (range, 0‐14.1). Conclusions: In high‐risk neuroblastoma, a novel, publicly available nomogram using prognostic biomarkers ( MYCN status, LDH, presence of bone marrow metastases; https://neuroblastoma.shinyapps.io/High-Risk-Neuroblastoma-Nomogram/ ) has the flexibility to apply a clinically suitable and context‐specific cutoff to identify patients at highest risk of death. This will facilitate testing urgently needed new frontline treatment options to improve outcome for these children.